Qawā‘id Al-Fiqhiyyah sebagai Tolak Ukur Penentuan Skala Prioritas Fiqhiyyah dalam Kehidupan Sehari-hari - Fatimah, Anggraini; Saputri, Eki; Khairunnisa, Khairunnisa; Fansuri, Muhammad Rayhan; Lisnawati, Lisnawati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study examines the role of Qawā‘id Fiqhiyyah (Islamic legal maxims) as a framework for determining the scale of priorities (Fiqh al-Awlawiyyāt) in the daily lives of Muslims. These maxims serve not only as tools for deriving Islamic legal rulings but also as normative guidelines that remain relevant to contemporary social dynamics. Using a descriptive qualitative method and a library research approach, this study analyzes various classical and contemporary sources, including the Qur’an, the Sunnah, and Islamic jurisprudence literature. The findings show that Qawā‘id Fiqhiyyah offer a practical framework for guiding Muslims to act wisely and in accordance with Sharia, especially in situations that require prioritization. The study also explains the methods for determining priorities through textual evidence (nass) and scholarly reasoning (ijtihad), and highlights several key maxims that emphasize balancing benefits and harms, as well as choosing between competing obligations.